Study of the influence of alloying elements on the mechanical characteristics and wear behavior of a ductile cast iron - Mohammed Iliasse Boulifa; Ali Hadji (Fracture and Structural Integrity)
In the present work, the influence of alloying elements, on the mechanical characteristics and wear behavior by modification of the chemical composition of the ductile iron was studied, to improve these characteristics for the manufacture of agricultural tractors parts in particular front and rear axles, ploughshares, gear crankcase, pinions, transmission shafts, crankshafts, etc... The cast iron investigated was prepared in an induction furnace at 1500C and inoculated by a ferro-silicon-magnesium to 45% Si and 10% Mg. The specimens were casted into self-hardening sand moulds at 1450C, after an addition of alloying elements, Manganese (0.6%), Nickel (0.5%), Molybdenum (0.2%), and Vanadium(0.1%) in the base spheroidal graphite cast iron produced. Various techniques including, optical microscopy, microhardness, hardness, tensile strength, impact resistance, and wear tests (wear resistance and friction coefficient) were used to characterize these specimens. The obtained results show that the tested samples have ductile iron structures formed by ferrite and pearlite. Moreover, mechanical and wear tests prove that the alloyed cast iron has improved characteristics compared to unalloyed cast iron and shows the positive effect of alloying elements on these characteristics.